Faktor yang Menumbuhkan Niat Berwirausaha Digital Siswa Program Keahlian Desain Komunikasi Visual: Factors That Foster Digital Entrepreneurial Intentions of Visual Communication Design Expertise Program Students - Arga, Bima Panji; Wrahatnolo, Tri; Agung, Achmad Imam (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
In today's digital era, digital entrepreneurial intentions among Visual Communication Design (DKV) students are increasingly crucial in preparing the younger generation to face technology-based economic challenges. This study aims to explore the influence of self-efficacy and self-management on digital entrepreneurial intentions of DKV students. The method used is an explanatory design and involves 150 DKV students of SMKN 1 Driyorejo who have participated in entrepreneurship learning, where data are collected through questionnaires filled out by DKV students at SMK. Statistical analysis used linear regression to assess the relationship between these variables. The results showed that innovation ability, self-efficacy, and self-management positively and significantly affect students' entrepreneurial intentions. The regression coefficient of each variable is 0.35 for innovation ability, 0.28 for self-efficacy, and 0.32 for self-management, with an overall contribution reaching 52%. The results showed that self-efficacy and self-management positively and significantly affect digital entrepreneurial intentions. Specifically, self-efficacy contributes more to shaping entrepreneurial intentions than self-management. This finding indicates that students who believe in their abilities are more motivated to start a digital business. The conclusion of this study emphasizes the importance of developing self-efficacy and management in the entrepreneurship learning program of DKV SMKN 1 Driyorejo students. Further development must be made through an entrepreneurship curriculum based on the Teaching Factory (Tefa). Suggestions for further research include exploring other factors that may influence digital entrepreneurial intentions and developing training programs that are more focused on the psychological aspects of entrepreneurship for students.